Casual effects of gut microbiota on risk of infections: a two-sample Mendelian randomization study - Lyu, Beibei; Ma, Jinghang; Bai, Yongyu; Feng, Zhen (Frontiers in Microbiology, 2023)
The correlation between gut microbiota and infections has garnered significant attention in previous studies; nevertheless, our understanding of the causal relationships and mechanisms between specific microbial species and infections remains limited.Methods: This study aimed to employ Mendelian randomization (MR) using single-nucleotide polymorphisms (SNPs) and genome-wide association study (GWAS) data of European ancestry to explore the genetic-level relationships between distinct types of gut microbiota and susceptibility to infections. Our analysis encompassed three prevalent infections: intestinal infections, pneumonia, and urinary tract infections, while concurrently examining various types of gut microbiota.We identified 18 protective gut microbiotas alongside 13 associated with increased infection risk. Particularly noteworthy are certain microbial communities capable of producing butyrate, such as the Ruminococcaceae and Lachnospiraceae families, which exhibited both favorable and unfavorable effects. Additionally, we observed a few certain communities linked to infection susceptibility, including ErysipelotrichaceaeUCG003 (OR=0.13, 95% CI: 0.054-0.33, P=1.24E-05), Collinsella (OR=3.25, 95% CI: 2.00-5.27, P=1.87E-06), and NB1n (OR=1.24, 95% CI: 1.09-1.40, P=1.12E-03).Conclusions: This study reveals complex relationships between gut microbiota and various infections. Our findings could potentially offer new avenues for exploring prevention and treatment strategies for infectious diseases.